Sensitivity of tumor cells towards CIGB-300 anticancer peptide relies on its nucleolar localization - Perera, Yasser (2012)
CIGB-300 is a novel anticancer peptide that impairs the casein kinase 2-mediated phosphorylation by direct binding to the conserved phosphoacceptor site on their substrates. Previous findings indicated that CIGB-300 inhibits tumor cell proliferation in vitro and induces tumor growth delay in vivo in cancer animal models. Interestingly, we had previously demonstrated that the putative oncogene B23/nucleophosmin (NPM) is the major intracellular target for CIGB-300 in a sensitive human lung cancer cell line. However, the ability of this peptide to target B23/NPM in cancer cells with differential CIGB-300 response phenotype remained to be determined. Interestingly, in this work, we evidenced that CIGB-300's antiproliferative activity on tumor cells strongly correlates with its nucleolar localization, the main subcellular localization of the previously identified B23/NPM target. Likewise, using CIGB-300 equipotent doses (concentration that inhibits 50% of proliferation), we demonstrated that this peptide interacts and inhibits B23/NPM phosphorylation in different cancer cell lines as evidenced by in vivo pull-down and metabolic labeling experiments. Moreover, such inhibition was followed by a fast apoptosis on CIGB-300-treated cells and also an impairment of cell cycle progression mainly after 5 h of treatment. Altogether, our data not only validates B23/NPM as a main target for CIGB-300 in cancer cells but also provides the first experimental clues to explain their differential antiproliferative response. Importantly, our findings suggest that further improvements to this cell penetrating peptide-based drug should entail its more efficient intracellular delivery at such subcellular localization.